1998
DOI: 10.1111/j.1746-1561.1998.tb00594.x
|View full text |Cite
|
Sign up to set email alerts
|

Middle School Students and Bicycle Helmet Use: Knowledge, Attitudes, Beliefs, and Behaviors

Abstract: Previous research has shown that bicycle helmet use among older children and adolescents continues to be low. This study determined middle school students' knowledge, attitudes, beliefs, and behaviors related to bicycle helmet use. Six middle schools in Hillsborough County, Fla., served as the research settings. A pretested survey instrument was administered to students. Overall, 3,333 sixth and seventh graders responded. Results showed that most children owned a bicycle, 38.1% owned a helmet, but only 15.8% w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Parental rules enforcing helmet use have also been found to be the single most important factor in influencing their children's choice to wear them (Miller et al, 1996). Additionally, having friends, siblings, and teachers who support, consistently wear, and have positive attitudes about wearing bicycle helmets has been shown to be a positive predictive factor in a child's use of a bicycle helmet (DiGuiseppi, Rivara, & Koepsell, 1990; Finnoff, Laskowski, Altman, & Diehl, 2001; Gielen et al 1994; Howland et al, 1989; Liller, Morissette, Noland, & McDermott, 1998; McLellan, Rissel, Donnelly, & Bauman, 1999; Otis et al, 1992).…”
Section: How To Promote Bicycle Helmets In Primary Carementioning
confidence: 99%
“…Parental rules enforcing helmet use have also been found to be the single most important factor in influencing their children's choice to wear them (Miller et al, 1996). Additionally, having friends, siblings, and teachers who support, consistently wear, and have positive attitudes about wearing bicycle helmets has been shown to be a positive predictive factor in a child's use of a bicycle helmet (DiGuiseppi, Rivara, & Koepsell, 1990; Finnoff, Laskowski, Altman, & Diehl, 2001; Gielen et al 1994; Howland et al, 1989; Liller, Morissette, Noland, & McDermott, 1998; McLellan, Rissel, Donnelly, & Bauman, 1999; Otis et al, 1992).…”
Section: How To Promote Bicycle Helmets In Primary Carementioning
confidence: 99%
“…Significantly more males than females never or rarely wore a helmet (34,48). Peer pressure, negative modeling by family members, and community climate are some of the factors related to nonuse (50,54). Building a culture of safety for seat belts and helmet-wearing among adolescents will be one of the future challenges (86).…”
Section: Seat Belts and Helmetsmentioning
confidence: 99%
“…Legislation has proved highly effective in increasing helmet use,8 and interventions have been identified that significantly improve helmet-wearing 9 10. In the absence of either legislation or intervention, helmet use has been found to be associated with parental encouragement,11 peer influences,11 12 children’s attitudes,13 – 16 and levels of neighborhood deprivation 10 17 18…”
mentioning
confidence: 99%